2021
DOI: 10.3390/molecules26113234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rice Straw Powder (RSP) Size and Pretreatment on Properties of FDM 3D-Printed RSP/Poly(lactic acid) Biocomposites

Abstract: To develop a new kind of environment-friendly composite filament for fused deposition modeling (FDM) 3D printing, rice straw powder (RSP)/poly(lactic acid) (PLA) biocomposites were FDM-3D-printed, and the effects of the particle size and pretreatment of RSP on the properties of RSP/PLA biocomposites were investigated. The results indicated that the 120-mesh RSP/PLA biocomposites (named 120#RSP/PLA) showed better performance than RSP/PLA biocomposites prepared with other RSP sizes. Infrared results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…The double-melting behavior was probably linked to the formation of different crystal structures, and the lower one corresponded to the melting of crystals with an imperfect structure. Similar phenomena were also described by Hao Liu et al [ 11 ] and Guim et al [ 21 ]. Endotherms in Figure 11 indicated that PLA/ROA composite specimens had well-defined glassy transition peaks centered at around 62.5 °C.…”
Section: Resultssupporting
confidence: 88%
“…The double-melting behavior was probably linked to the formation of different crystal structures, and the lower one corresponded to the melting of crystals with an imperfect structure. Similar phenomena were also described by Hao Liu et al [ 11 ] and Guim et al [ 21 ]. Endotherms in Figure 11 indicated that PLA/ROA composite specimens had well-defined glassy transition peaks centered at around 62.5 °C.…”
Section: Resultssupporting
confidence: 88%
“…Guo et al [ 23 ] fabricated the WF/PLA biocomposites with FDM and discussed the effect of toughening agents on the properties of the printed specimens, and the impact strength of the biocomposites were increased by 51.31% when 10 wt% thermoplastic polyurethane as the toughening agent was used. Yu et al [ 24 ] developed a new kind of environmentally friendly composite filament for FDM 3D printing based on RSP/PLA biocomposites, exploring the effects of the RSP size and pretreatment on the properties of the printed samples, when RSP was synergistically pretreated by alkaline and ultrasound, the composite exhibited the increased mechanical properties, thermal stability, and hydrophobic properties than untreated RSP/PLA. Yu et al [ 25 ] also experimented the effects of the soil burial of rice straw on the morphology and properties of 3D-printed RSP/PLA biocomposites, and they concluded that, more cavities with large holes could be observed on the surfaces of the samples with the extension of soil burial time of rice straw.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that a sample with 5 mm thick and 100 fill density aborded higher sound frequency. Yu et al [ 163 ] investigated the mechanical and thermal stability of rice straw powder/PLA composites. The composites were made using filler particles of different mesh sizes (60, 120, 160 and 200).…”
Section: Fdm Compositesmentioning
confidence: 99%
“…Yu et al [ 163 ] investigated the water absorbing qualities of rice straw powder/PLA composite. The composites were made using filler particles of different mesh sizes (60, 120, 160, and 200).…”
Section: Fdm Compositesmentioning
confidence: 99%